The Relationship of Historical Learning Video Media With History Learning Results of Class XI Students at SMA Negeri 1 Central Lampung Rumbia 2019/2020 Academic Year - Nyoman Suwita (FKIP UNIVERSITAS LAMPUNG, 2020)
ABSTRACT Education is an important thing in life. Education absolutely must be given to every human being. Therefore, teachers are required to be able to design and implement learning experience programs appropriately so that students gain complete knowledge so that the learning process becomes meaningful for students. The formulation of the problem in this research is